Tahfidz Al-Quran Learning as a Leading Program at MTs Al Ghozaly Siwatu Wonosobo - Akimudin, Akimudin; Hamzah, Muchotob; Suyud El Syam, Robingun (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
The purpose of this research is to analyze the learning of Al-Qur'an memorization as a leading program at MTs Al Ghozaly Siwatu Wonosobo. This field research uses a qualitative approach with a case study method, involving participant observation, in-depth interviews, and documentation analysis. The results of the study indicate that the Al-Qur'an memorization program at MTs Al Ghozaly Siwatu Wonosobo has been running in a structured manner for three years, with varied learning methods and a continuous evaluation system. The success of this program is supported by a religious Islamic boarding school environment, competent tahfidz teachers, an integrated curriculum, as well as student motivation and active support from parents. The existence of a tahfidz quarantine program as a continuation for outstanding students shows the institution's commitment to producing Al-Qur'an memorizers continuously. This program not only improves students' memorization abilities, but also forms positive characters of discipline, responsibility, and sincerity. As a leading program, Al-Qur'an memorization has become the identity of the madrasah and the main attraction for the community towards Islamic education based on character and spirituality. We support the sustainability of the program, madrasahs are advised to improve infrastructure and develop an evaluation system that touches on aspects of understanding and implementing the values of the Qur'an. Teachers are expected to continue to develop methods that are in accordance with the character of students and strengthen relationships with parents, students need to maintain enthusiasm in memorizing. Further research is recommended to expand the study of the long-term impact of the tahfidz program, as well as to establish collaboration with other tahfidz institutions as an effort to strengthen the quality of Islamic education based on the Qur'an.